Cross-linguistic influence among Chinese learners of English (L2) and German (L3) - Tan, C (2023)
Chinese, English and German have different word orders. The word order in English and Chinese is largely Subject-Verb-Object (SVO). However, the Chinese word order is more flexible, so Chinese sentences are sometimes presented as Subject-Object-Verb (SOV). The SVO order is simpler than the verb second (V2) word order system in German, which requires one of other fragments to exist before the verb in a sentence to ensure that the verb always occurs in the second position in the sentence (In subordinate clauses in German, the verb position does not fulfil the verb second rule). As such, the word order of the three languages is sometimes identical, sometimes completely different, and sometimes pairwise similar. This study aimed to investigate the effects of Chinese as a first language (L1) and English as a second language (L2) on Chinese learners’ acquisition of the German word order. 30 sentences with different word orders across the three languages were selected for a set of novel multiple-choice tasks, during which participants had to choose the correct option to make the sentence having the correct word order. The task was completed by 27 undergraduate students (L1 Chinese, L2 English, L3 German) who majored in German studies and had English learning experience before attending university. The results showed that participants’ knowledge of both Chinese and English had a positive effect on the acquisition of German word order and that the participants’ L2 and L3 proficiency levels were not correlated with their performance in the L3 word order tasks and their L2 and L3 proficiency levels were not correlated neither. Based on these findings, it is believed that when the L1 and L2 word order is the same, participants do not tend to generalise this pattern to the L3 regardless of how proficient in their background languages they are.